Evaluation of the Marine Algae Gracilaria and its Activated Carbon for the Adsorption of Ni(II) from Wastewater - A. Esmaeili; P. Beirami; S. Ghasemi (E-Journal of Chemistry)
The batch removal of Ni2+ from aqueous solution and wastewater using marine dried (MD) red algae Gracilaria and its activated carbon (AC) was studied. For these experiments, adsorption of Ni2+ was used to form two biomasses of AC and MD. Both methods used different pH values, biomass and initial concentration of Ni2+. Subsequently adsorption models and kinetic studies were carried out. The maximum efficiencies of Ni2+ removal were 83.55% and 99.04% for MD and AC respectively developed from it. The experimental adsorption data were fitted to the Langmuir adsorption model. The nickel(II) uptake by the biosorbents was best described by pseudo-second order rate model. The kinetic studies showed that the heavy metal uptake was observed more rapidly by the AC with compared to MD. AC method developed from MD biomass exhibited higher biosorption capacity. Adsorption capacity is related to the pH of solution, pH 5.0 is optimal for nickel. The maximum efficiencies of Ni2+ removal were for AC method. The capacity is related to the pH of solution, pH 5.0 is optimal for nickel. The equilibrium adsorption data are correlated by Langmuir isotherm equation. The adsorption kinetic data can be described by the second order kinetic models